GE_GERICHTE C/20740/2013 vom 25. August 2015 - GE Cour de justice (2015)
RÉSILIATION IMMÉDIATE; CONTRAT DE TRAVAIL; INCAPACITÉ DE TRAVAIL; DÉLAI DE RÉSILIATION; DOMMAGE; VACANCES | CO.337.1; CO.337.2; CO.337.3; CO.337c.1; CO.336c.1.a; CO.337c.3; CO.321e; CO.329a.1